(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
In the era of rapid digital transformation, cyber-socialization has emerged as a fundamental factor in shaping the personality and communicative patterns of Generation Z. This study investigates the socio-psychological impact of digital environments on intergenerational communication, specifically focusing on the differences between students (Gen Z) and teachers. Through a quantitative study of 100 respondents in Tashkent, the research explores how internet usage intensity correlates with communicative competence and interpersonal distancing. Results indicate a significant “digital divide” where Gen Z prioritizes virtual interaction, leading to cognitive dissonance during face-to-face communication with older generations. The findings suggest that controlled digital literacy and psychological intervention programs can bridge this gap.